Investigation of Inhibitory Effect of the Aloe Vera Extract on Corrosion of Aluminium Alloys - Šćepanović, Jelena; Herenda, Safija; Radonjić, Dragan; Vuksanović, Darko (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2019)
This paper considers the inhibition effect of Aloe Vera on the selected aluminium alloys in 10 % sulfuric acid and 3 % sodium chloride solutions at room temperature, using methods of potentiodynamic polarisation and cyclic voltammetry. The study involved as-cast and heat-treated 2xxx alloys, with the scanning speed of 1mV/s for linear polarisation and 50 mV/s for cyclic voltammetry. The various constant potential was applied for each tested alloy. Polarisation results indicate that the transpassivation occurs in an acid medium in case of each alloy. The obtained results indicate that Aloe vera extract acts as a cathodic inhibitor.